Can environmental protection tax drive manufacturing carbon unlocking? Empirical evidence from China - Wen, Limin; Sun, Shufang (Frontiers in Ecology and Evolution, 2023)
China's environmental protection tax policy has emerged as a pivotal force in steering the country towards reduced pollution and carbon emissions. This study focuses on evaluating the impact of the environmental protection tax on carbon unlocking within the manufacturing industry, offering crucial insights to address the dual challenges of industry development and carbon emission reduction. Utilizing Chinese provincial panel data spanning from 2004 to 2020, we gauge the carbon unlocking efficiency of the manufacturing industry using the super-efficiency slacks-based measure (SBM) model with undesired outputs. Additionally, we empirically examine the impact of the environmental protection tax policy on manufacturing carbon unlocking through the propensity score matching difference-in-differences (PSM-DID) model. Our findings indicate a significant enhancement in the carbon unlocking efficiency of the manufacturing industry due to the implementation of the environmental protection tax policy. Compared with the provinces (municipalities) that did not raise the environmental protection tax rate standard, the carbon unlocking efficiency of manufacturing in the provinces (municipalities) that raised the environmental protection tax rate standard increased by 11.6%, and the dynamic effect shows that the policy effect increases gradually over time. Further mechanism tests reveal that an environmental protection tax improves manufacturing carbon unlocking efficiency mainly by stimulating manufacturing firms to increase environmental protection investment and green technology innovation. Moreover, there is heterogeneity in the policy effect of the environmental protection tax, and its impact on manufacturing carbon unlocking is more significant in the central and western regions and regions with higher levels of legalization. Therefore, we should adhere to the policy orientation of low-carbon development in manufacturing, accelerate green technological innovation in manufacturing, and coordinate the special advantages of each region according to local conditions to bring into play the role of an environmental protection tax in reducing carbon and improving efficiency.